Trachoma Mapping in Gombe State, Nigeria: Results of 11 Local Government Area Surveys. (1st November 2016) - Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed Dantani; Muazu, Habila; Umar, Murtala Muhammad; Alada, Joel; Onyebuchi, Uwazoeke; Olamiju, Fracisca; Isiyaku, Sunday; William, Adamani; Willis, Rebecca; Flueckiger, Rebecca Mann; et al.
ABSTRACT: Purpose : To determine the need or otherwise for establishment of a trachoma elimination program in Gombe State, Nigeria, by estimating the population-based prevalence of trachoma in each Local Government Area (LGA) of Gombe. Methods : Using a multi-stage, systematic, random, and quasi-random sampling approach and Global Trachoma Mapping Project support, we selected 25 clusters in each LGA. In each cluster, we selected 25 households and all consenting residents aged 1 year and older were examined for trachomatous inflammation–follicular (TF) and trichiasis, using the World Health Organization simplified grading scheme. Results : No LGA in Gombe State had a TF prevalence ≥5% in 1–9-year-olds. All LGAs had trichiasis prevalences above the elimination threshold and should be targeted for community-based delivery of trichiasis surgery. Only three LGAs had household-level improved wash water access of greater than 80%. Access to improved sanitation facilities was also poor as household access to improved sanitation facilities was above 80% in only one LGA. Conclusion : A trachoma program focused on delivery of trichiasis surgery is required in Gombe. Improvements in water and sanitation, through engagement with other sectors, are necessary.